(untitled) - Svancara, Theresa (Chicago, 2002)
Questions and answers provide information about a variety of echinoderms, including the sea star, sea urchin, and sea cucumber.
Includes bibliographical references (p. 64) and index.
Keywords: Juvenile literature; Echinodermata; Starfishes; Juvenile literature